Effect of sintering condition on the properties of Silicate ceramic materials - Muhamad Hanifa Mohamad (Universiti Malaysia Perlis, 2008)
This study addresses the effects of fabrication techniques on the development of mechanical properties of sintered clay ceramics. The influence of thermal treatment, soaking time and firing temperature, were investigated in order to optimize the fabrication process and to obtain the enhanced mechanical properties. Single clay raw material such as kaolin, ball clay and silica were used for this study. Samples were uniaxially pressed in a rectangular shape and sintered to temperature ranging from 1000 °C to 1400 °C sintering temperature at various soaking time. The variation of flexural strength and compression strength starting from 1000 °C to 1400 °C temperature with heating rate 5 °C/min was also presented. In addition, the density, porosity and shrinkage of the sintered samples also have been determined. Mechanical properties characterization was performed by means of three-point bending tests and compression test. The sample were also been analyzed using Scanning Electron Microscope (SEM) to observe the microstructure of the sample. From all experiment and testing, it is found that by increasing of sintering temperature will decreased the percent of porosity in ceramic sintered sample and at the same the same time increased the bulk density and flexural strength of the ceramic sample. In this study, the results proved that high soaking time in the early stage of firing has influence on densification and the resulting mechanical properties of ceramic materials.